Synthesis of Cyclohexa-1,3-dienamines by Formal [3+3] Cycloaddition - Toum, Valérie; Lhommet, Gérard; Dechoux, Luc (Synlett, 2012)
Formal [3+3] cycloadditions of β-carboxymethylenamino esters with acrolein derivatives give a range of cyclohexa-2,6-dicarboxymethyl-1,3-dienamines that are potential acceptor–donor–acceptor systems.
Keywords: multicomponent reactions; cyclohexa-1,3-dienamines; [3+3] cycloaddition; donor–acceptor systems